Perceived causes of infertility among Women of child bearing age in Ilorin West Local Government Area, Kwara State - Jidda, K. A.; Jamiu, A. T.; Abdulrasaq, Q. O.; Kperogi, I. I.; Edungbola, A. A.; Obaditan, O. F. (NIU Journal of Humanities, 2018)
This study investigated the Perceived causes of infertility among women of child bearing age in Ilorin West Local Government, Kwara State. Infertility is a disease of the reproductive system defined by the failure to achieve a clinical pregnancy after 12 months or more of regular unprotected regular sexual intercourse. This study investigated (i) Smoking and (ii) STI as a cause of Infertility among Women of Child bearing age. A descriptive research design of survey method was employed for this study. The population consists of all women of child bearing age in Ilorin West Local Government. A multistage sampling technique was used to select 241 respondents. Researcher’s structured questionnaire which was validated by three experts from the Department of Health Promotion and Environmental Health Education, Faculty of Education, University of Ilorin was used for data collection. A correlation co-efficient of .78 ‘r’ was obtained through test re-test method using Pearson Product Moment Correlation. Data collection was conducted by the research and three trained research assistants. The postulated null hypotheses were tested using inferential statistics of chi-square at 0.05 alpha level. The findings from this study showed that: Smoking will significantly be perceived as a cause of infertility among women of child bearing age with the calculated chi-square (χ 2 ) value of 172.66 is greater than the table chi-square (χ 2 ) value of 16.92 at the degree freedom (df) 9 Sexually Transmitted infections will significantly be perceived as a cause of infertility among women of child bearing age with the calculated chi-square (χ 2 ) value of 192.49 is greater than the table chi-square (χ 2 ) value of 16.92 at the degree freedom (df) 9 Based on the findings of the study, it was concluded that smoking and sexually transmitted infections were significantly perceived as causes of infertility among women of child bearing age in Ilorin West Local Government, Kwara State. Therefore, it was recommended that Health workshops should be organized to enlighten women in Ilorin West Local Government about the dangers involve in smoking and its effect on fertility and the knowledge of causes and prevention of STIs should be spread among women in order to curb the problem of infertility.